Essence, Explanation, and Modality. (28th October 2020) - Wallner, Michael; Vaidya, Anand
Abstract: Recently, Kit Fine's (1994 ) view that modal truths are true in virtue of, grounded in, or explained by essentialist truths has been under attack. In what follows we offer two responses to the wave of criticism against his view. While the first response is pretty straightforward, the second is based on the distinction between, what we call, Reductive Finean Essentialism and Non-Reductive Finean Essentialism . Engaging the work of Bob Hale on Non-Reductive Finean Essentialism, we aim to show that the arguments against Fine's view are unconvincing, while we acknowledge the presence of a deep standoff between the two views.